The Many Faces of National Security in the Arab World
XXV, 322 p.
Keywords: Two Gulf wars and the continuing Arab-Israeli conflict have highlighted the salience of military factors in the Middle East. This book argues, however, that many of the most serious 'security' challenges to Arab states and societies are rooted not in external military threats but in the imperatives of socio-economic development. Contributors examine the regional security environment; the social and political impact of regional militarization; and underdevelopment as a source of regional insecurity.